A Property of Mr. Harrod's Dynamic Model - Newman, Peter (Review of Economic Studies, 1954)
Journal Article A Property of Mr. Harrod's Dynamic Model Get access Peter Newman Peter Newman Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 22, Issue 1, 1954, Pages 70–71, https://doi.org/10.2307/2296227 Published: 01 January 1954